Evaluasi Implementasi Kebijakan Asas Cabotage dalam Perkembangan Industri Pelayaran Nasional - Jener Alison; L. Denny Siahaan; Endang Sugiharti (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
Implementation of Cabotage Principle Policy in National Shipping Industry Development. This undertaken research based on nonoptimal implementation of cabotage principle policy in shipping industry, the policy related to shipping activities such as port load both passengers and commodities operated by national shipping company, substandard quality and quantity of port infrastructure and inadequate productivity of national company. This is a descriptive observation accomplished with qualitative approach. According to this research, the implementation of cabotage principle policy in the trade sector, the policy support the growth of national shipping industry, it could be observed that there are more national ships in the ports; in the transportation sector, the policy allowed growing shipping stakeholders to support local port activities effectively even in a small scale compared to other Asian countries; the implementation of the policy to industry sector, led the growth of national shipyard company with less consideration because domestic shipyard quite expensive and depend on import component.